Corpus Linguistics and Translation Studies: Interaction and Reaction - Olohan, Maeve (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This paper focuses on one particular parallel development in linguistics and translation studies, namely corpus-based analysis of language use. Recent years have seen the compilation of corpora of translations, designed specifically to investigate the language and features of translation, usually by comparing translations with non-translations. Some of the interactions between corpus linguistics and corpus-based translation studies are traced in terms of perceptions of translated texts and underlying assumptions of corpus-based studies. Corpus-based translation studies is placed in the con¬text of current theoretical trends in translation studies and, through brief re¬ference to research which has aimed to investigate potential features of translation, attention is drawn to the importance of contextualising translation by combining corpus-based investigations with other kinds of methodologies and analyses.